EXPERIMENTAL AND NUMERICAL STRESS ANALYSIS OF INVOLUTE SPLINED SHAFT (Journal of Engineering, 2012)
In this study, the induced splined shaft teeth contact and bending stresses have been investigated numerically using finite element method(Ansys package version 11.0) with changing the most effecting design parameter,(pressure angle, teeth number, fillet radius and normal module), for internal and external splined shaft. Experimental work has been achieved using two dimensional photoelastic techniques to get the contact and bending stresses; the used material is Bakelite sheet type “PSM-4”.The results of numerical stress analysis indicate that, the increasing of the pressure angle and fillet radius decrease the bending stress and increase the contact stress for both internal and external spline shaft teeth while the increasing of the normal module and teeth number decrease the contact and bending stresses